2001
DOI: 10.1073/pnas.051631898
|View full text |Cite
|
Sign up to set email alerts
|

Genetically altered AMPA-type glutamate receptor kinetics in interneurons disrupt long-range synchrony of gamma oscillation

Abstract: Gamma oscillations synchronized between distant neuronal populations may be critical for binding together brain regions devoted to common processing tasks. Network modeling predicts that such synchrony depends in part on the fast time course of excitatory postsynaptic potentials (EPSPs) in interneurons, and that even moderate slowing of this time course will disrupt synchrony. We generated mice with slowed interneuron EPSPs by gene targeting, in which the gene encoding the 67-kDa form of glutamic acid decarbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 45 publications
3
74
0
Order By: Relevance
“…This indicated that the response to TS was more stable across time for KA-responsive EGFP ϩ neurons than for AMPAresponsive EGFP ϩ neurons. Because modeling studies predict that the frequency of network oscillations depends in part on the time course of synaptic currents in interneurons (Traub et al, 1996;Wang and Buzsaki, 1996;Fuchs et al, 2001), we next hypothesized that the specific EPSP KA kinetics could partly provide the O-LM interneuron type with their selective activation at theta. In keeping with this hypothesis, the decay time constants of averaged EPSPs in O-LM cells were indeed slower (40 Ϯ 9 ms; n ϭ 5; p Ͻ 0.05) than those in EGFP ϩ /non-O-LM cells (22 Ϯ 3 ms; n ϭ 8; p Ͻ 0.05), whereas input resistance was comparable in both cell types (139 Ϯ 11 and 145 Ϯ 10 M⍀, respectively; p Ͼ 0.1).…”
Section: Efficient Epsp Ka -Spike Coupling In O-lm Cells Stimulated Amentioning
confidence: 99%
“…This indicated that the response to TS was more stable across time for KA-responsive EGFP ϩ neurons than for AMPAresponsive EGFP ϩ neurons. Because modeling studies predict that the frequency of network oscillations depends in part on the time course of synaptic currents in interneurons (Traub et al, 1996;Wang and Buzsaki, 1996;Fuchs et al, 2001), we next hypothesized that the specific EPSP KA kinetics could partly provide the O-LM interneuron type with their selective activation at theta. In keeping with this hypothesis, the decay time constants of averaged EPSPs in O-LM cells were indeed slower (40 Ϯ 9 ms; n ϭ 5; p Ͻ 0.05) than those in EGFP ϩ /non-O-LM cells (22 Ϯ 3 ms; n ϭ 8; p Ͻ 0.05), whereas input resistance was comparable in both cell types (139 Ϯ 11 and 145 Ϯ 10 M⍀, respectively; p Ͼ 0.1).…”
Section: Efficient Epsp Ka -Spike Coupling In O-lm Cells Stimulated Amentioning
confidence: 99%
“…Several findings suggest that inhibitory interneurons play a critical role in the generation of rhythmic, synchronized activity (Cobb et al, 1995;Fuchs et al, 2001;Whittington and Traub, 2003). For example, activation of muscarinic or kainite receptors induces synchronous gamma frequency rhythms that involve fast-spiking (FS) inhibitory interneurons (Traub et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma oscillations have received special attention in the research of neuropsychiatric disorders due to their alleged role in sensory binding, selective attention, associative and perceptual learning, encoding and retrieval of memory traces (Singer, 1993, Bragin et al, 1995, Chrobak and Buzsaki, 1998, Miltner et al, 1999. Gamma-band oscillations depend on intact function of the fast-spiking GABAergic (parvalbumin containing) interneurons (Fuchs et al, 2001). These subsets of inhibitory GABAergic interneurons, located in hippocampal and cortical areas, are proposed to play a primary role in the generation of the gamma oscillations (Uhlhaas and Singer, 2010).…”
Section: Erp Measurements and Analysismentioning
confidence: 99%